Neurocognitive outcomes in children with unilateral basal ganglia arterial ischemic stroke and secondary hemidystonia. Issue 7 (3rd October 2018) - Westmacott, Robyn; McDonald, Kyla P.; deVeber, Gabrielle; MacGregor, Daune; Moharir, Mahendranath; Dlamini, Nomazulu; Askalan, Rand; Williams, Tricia S.
ABSTRACT: Dystonia is a movement disorder that involves excessive, involuntary muscle contractions resulting in repetitive movements and/or abnormal posturing. One common cause of unilateral dystonia in childhood is ischemic stroke involving the basal ganglia and/or thalamus. Virtually nothing is known about neuropsychological outcomes in children who have dystonia following basal ganglia stroke. The present study explored whether or not children with secondary dystonia experience additional cognitive challenges when compared to children with similar patterns of brain injury, but no dystonia. We examined intellectual function, academics, and several aspects of executive function in children with unilateral basal ganglia stroke during childhood, comparing those with dystonia and those without. Although groups did not differ in terms of lesion size, we found significantly lower performance on measures of verbal and nonverbal reasoning, inhibitory control, and academic ability in children with secondary dystonia compared to those without. In contrast, there were no significant group differences on parent ratings of their child's executive function in daily life. These findings suggest that maladaptive reorganization following basal ganglia stroke may contribute to the development of secondary dystonia and also to poor intellectual and academic outcomes in this group.